ANALISIS IT STRATEGIC PLANNING (ITSP) PADA PT. X DENGAN PENDEKATAN MODEL SWOT - Fuad Mumtas (Jurnal Informatika dan Bisnis, 2014)
Since it was realized that the information has become one of the important production factor and is crucial for a company that wants to win the competition in today's global era. The management company felt the need to establish a reliable enterprise information systems. For a company that has quite a modern building and implementing information systems, information systems development process has become a normal activity that is sustainable, in the sense of the word management sometimes does not feel the need to draw up a formal document containing the information systems strategic plan in detail. But for most companies who just intend to build information systems, management felt the need to draw up a document that contains the IT Strategic Planning (ITSP) guides the development of the enterprise information systems. SWOT analysis is the analysis of the internal and external conditions of an organization which would then be used as a basis for designing strategies and work programs. Internal analysis of the factors include StrengthÂ  and Weakness. Meanwhile, the analysis of external factors include Opportunity and Threath.